Media portrayal of obese female actors on local Philippine television - HEIMBROD, MA. CAMILLE CARMINIA (Archīum Ateneo, 2019)
This study used Dyers Theory on Stereotypes (1979) in understanding how the media portrays and stereotypes obese female actors on local Philippine television. Protocols from Hatchs inductive analysis was also used to determine the negative and positive portrayals, as well as the anti-fat attitudes toward Karla Estrada and Sharon Cuneta that exist in Magandang Buhay and The Voice.This study found that there are still limited portrayals of obese female actors on local Philippine television today. Even though the negative portrayals and stereotypes may not be generalized for both television shows, it is evident that negative portrayals of obese actors still outweigh positive portrayals on television.